Políticas públicas para a formação educacional e promoção de consumo ambientalmente sustentável - Boza, Daniela (2020)
Although there is a great demand for environmentally friendly products, these still represent a low percentage in relation to global purchase. With this bias, this dissertation is based on questioning whether Brazilian legislation is efficient to the point of raising awareness and influencing sustainable consumer behavior through educational actions. This research has two main objectives: (i) To know and analyze studies that address the use of public policies for educational training focused on the promotion of pro-environmental citizens; and (ii) Know the opinion of specialists in the region where the Postgraduate Program in Environmental Sciences - PPGCiamb is inserted on the relevance of public policies to promote educational practices aimed at promoting environmentally sustainable consumption. To achieve the first objective, a search was made for articles, theses and dissertations that addressed the use of public policies in basic education as an example of pedagogical practices. The results show that Environmental Education and Public Policies on the Environment are inserted in the classroom through theoretical and practical methodologies, while the Legislation, is not worked directly. To achieve the second objective, the direct technique was used through in-depth interviews with six specialists. The results show the strength that education has in acquiring knowledge, raising awareness and awakening a responsible commitment to this environmental theme. It also shows the need to include environmental education in school curricula, not only as a specific subject, but through the interdisciplinarity that the theme provides. This research allowed us to conclude that the Brazilian Legislation is seen as the main influencer for sustainable consumption, although it is not proving to be efficient. Their contributions recur both for the environmental and educational areas, and it is suggested to deepen studies and research in loco with professionals from different areas of knowledge in relation to environmental legislation, composing the curricular matrix of schools (public and private) and universities.